Examining the Role of Power-Control Theory and Self-Control to Account for Computer Hacking. - Holt, Thomas J.; Steinmetz, Kevin F. (Crime & Delinquency, 2021)
Criminological inquiry consistently identifies a gender difference in offending rates, which are also evident among certain forms of cybercrime. The gender difference in cybercrime offending is particularly large within computer hacking, though few have specifically addressed this issue through applications of criminological theory. The current study attempted to account for the gender disparity in hacking through a test of power-control theory, which considers the role of class and family structure. This analysis also incorporated an extension of power-control theory through the influence of low self-control. Using data from the Second International Self-Report of Delinquency study (ISRD-2), logistic regression analyses were estimated, producing partial support for both theories to account for hacking. Implications for theory and research were explored in detail.